The Preclinical Pharmacological Study of a Novel Long-Acting Local Anesthetic, a Fixed-Dose Combination of QX-OH/Levobupivacaine, in Rats - Zhang, YuJun; Yin, QinQin; Gong, DeYing; Kang, Yi; Yang, Jun; Liu, Jin; Zhang, WenSheng (Frontiers in Pharmacology, 2019)
Previous studies demonstrated that 35 mM QX-OH/10 mM Levobupivacaine (LL-1), a fixed-dose combination, produced a long-acting effect in rat local anesthesia models. All preclinical pharmacodynamic results indicated that LL-1 had potential for postsurgical pain treatment. The objective of this study was to investigate the pharmacokinetics of LL-1. Then, the possible mechanism of the extended duration by the combination was examined. The compound action potentials were recorded to verify the pharmacodynamic result in ex vivo. In frog sciatic nerve, LL-1 produced an effective inhibition with rapid onset time. The concentration-time profiles of LL-1 were determined in plasma and local tissues after sciatic nerve block. The maximum concentration of QX-OH and levobupivacaine were 727.22 ± 43.38 μg/g and 256.02 ± 28.52 μg/g in muscle, 634.26 ± 36.04 μg/g and 429.63 ± 48.64 μg/g in sciatic nerve, and 711.71 ± 25.14 ng/mL and 114.40 ± 10.19 ng/mL in plasma, respectively. The absorption of QX-OH into circulation was very rapid at 0.71 ± 0.06 h, which was faster than that of levobupivacaine (4.11 ± 0.39 h, p = 0.003). The half-time of QX-OH in plasma and local tissues had no significant difference (p = 0.329), with the values of 2.64 h, 3.20 h, and 3.79 h in plasma, muscle, and sciatic nerve, respectively. The elimination profile of levobupivacaine differed from that of QX-OH, which was slower eliminated from plasma (4.89 ± 1.77 h, p = 0.036) than from muscle (1.38 ± 0.60 h) or sciatic nerve (1.28 ± 0.74 h). When levobupivacaine was used alone, the Tmax in plasma was 1.07 ± 0.16 h. Interestingly, the Tmax of levobupivacaine in the plasma was increased by four times in combination with QX-OH (4.11 ± 0.39 h). Levobupivacaine promotes cellular QX-OH uptake. In conclusion, the preclinical pharmacokinetic study of LL-1 in the rat plasma, muscle, and sciatic nerve was accomplished. Then, the possible mechanism of the prolonged duration was that QX-OH delayed the absorption of levobupivacaine from the injection site into circulation, and levobupivacaine accelerated QX-OH to accumulate into cells.